Deep blue diboron embedded multi-resonance thermally activated delayed fluorescence emitters for narrowband organic light emitting diodes - Rayappa Naveen, Kenkera; Lee, Hyuna; Braveenth, Ramanaskanda; Joon Yang, Ki; Jae Hwang, Soon; Hyuk Kwon, Jang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •Newly synthesized diboron embedded deep blue MR-TADF emitters.•Narrow spectra with FWHM of 14 nm and CIE y coordinate below 0.10.•Small △EST (≤0.07 eV), high PLQY, and good TADF performances.•All these materials show high EQEs (>33%) We report three deep blue multiple resonant TADF emitters,m-ν-DABNA, 4F-ν-DABNA,and4F-m-ν-DABNAby incorporating methyl groups and fluorine atoms in diboron basedν-DABNA core. The introduction of methyl groups at para positions to the boron atoms and fluorine atoms atorthopositions to the nitrogen atoms resulted in bandgap enhancement by electron donating and electron withdawing effects. All three emitters exhibit pure blue emissions with high photoluminescence quantum yield around ∼ 90%, small ΔEST (≤0.07 eV) values, and fast reverse intersystem crossing rate (kRISC). Fabricated OLEDs with these emitters show excellent external quantum efficiency over 33%. Among three materials,4F-ν-DABNAand4F-m-ν-DABNAexhibit the CIE y coordinate of 0.08 and 0.06, respectively. Our current material design approach guides a path for the development of deep blue TADF emitters for highly efficient narrowband OLEDs.